Helicobacter pylori causes gastric dysbacteriosis in chronic gastritis patients - Cen Chao; Du Qiuying; Luo Bin; Wang Tonghua; Su Jianwei; Qin Xiaoshan; Zhang Wenyan; Lu Lijing; Liao Yang; Huang Yanqiang; Liang Yumei (Open Life Sciences, 2024)
Gastric mucosal samples were procured and underwent the sequencing of 16S ribosomal RNA (16S rRNA) via Illumina high-throughput sequencing technology to explore the impact of Helicobacter pylori (H. pylori) infection on the composition of gastric flora in chronic gastritis (CG) patients. In the results, the operational taxonomic unit (OTU) analysis revealed an overlap of 5706 OTUs shared between the two groups. The top 5 abundance ranking (TOP5) phyla comprised Bacteroidetes, Proteobacteria, Firmicutes, Actinobacteria, and Epsilonbacteraeota, while the TOP5 genus was Lachnospiraceae_NK4A136_group, Helicobacter, Bacteroides, Klebsiella, and Pseudomonas. In the metabolic pathways at the Kyoto Encyclopedia of Genes and Genomes (KEGG)_L3 level, conspicuous variations across seven functions were observed between the H. pylori-positive (HP_Pos) and H. pylori-negative (HP_Neg) groups. Subsequently, functional gene enrichment in KEGG pathways was further validated through animal experimentation. In contrast to the mice in the HP_Neg group, those infected with H. pylori manifested an infiltration of inflammatory cells, an augmentation in gastric acid secretion, and conspicuously elevated scores regarding gastric activity, along with heightened levels of malondialdehyde. In conclusion, CG patients infected with H. pylori displayed a disorder in gastric flora, furnishing a theoretical basis for the prophylaxis of H. pylori infection and its associated pathogenic ramifications.